Impact of Insolation on Melatonin, Sleep Disorders, Cerebral Ischemia, and Cognitive Functions - Adambaev Zufar; Yakubova Markhamat; Olmosov Ravshan (BIO Web of Conferences)
The article explores the effect of insolation on the level of serum melatonin, sleep disorders, chronic cerebral ischemia and cognitive functions. Eighty patients with chronic cerebral ischemia (CCI) were examined. The average age of the patients was 58.5±1.4 years. The patients were divided into 6 groups depending on the presence of sleep disorders and the stage of CCI. The concentration of melatonin in the blood was studied depending on the season. Sleep disorders and cognitive impairment were assessed using special questionnaires, and cognitive evoked potentials P300 were studied. To correct sleep disorders, patients took melatonin. The concentration of melatonin in the blood is subject to seasonal changes in the duration of daylight, with maximum values in winter and minimum in summer. With increasing age and severity of cerebral ischemia, a decrease in the concentration of melatonin in the blood is observed. As the severity of CCI increases, cognitive indices deteriorate, as indicated by questionnaires and cognitive evoked potentials, which show an increase in P300 latency. Additionally, daytime sleepiness, as measured by the Epworth scale, also tends to worsen. Sleep disturbance in patients with CCI leads to a decrease in cognitive functions.